2008
DOI: 10.1152/jn.01188.2007
|View full text |Cite
|
Sign up to set email alerts
|

Shape Selectivity in Primate Frontal Eye Field

Abstract: Peng X, Sereno ME, Silva AK, Lehky SR, Sereno AB. Shape selectivity in primate frontal eye field. J Neurophysiol 100: 796 -814, 2008. First published May 21, 2008 doi:10.1152/jn.01188.2007. Previous neurophysiological studies of the frontal eye field (FEF) in monkeys have focused on its role in saccade target selection and gaze shift control. It has been argued that FEF neurons indicate the locations of behaviorally significant visual stimuli and are not inherently sensitive to specific features of the visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 80 publications
7
46
0
Order By: Relevance
“…However, the visual capabilities of FEF neurons may be underappreciated. Reports have found feature selectivity in FEF (e.g., Bichot et al 1996;Peng et al 2008) and support a role for it in top-down control of feature attention (Zhou and Desimone 2011).…”
Section: Behavioral Implications Of Remappingmentioning
confidence: 89%
“…However, the visual capabilities of FEF neurons may be underappreciated. Reports have found feature selectivity in FEF (e.g., Bichot et al 1996;Peng et al 2008) and support a role for it in top-down control of feature attention (Zhou and Desimone 2011).…”
Section: Behavioral Implications Of Remappingmentioning
confidence: 89%
“…This is not the first observation of noncorrespondence in shape selectivity. In a frontal eye field study where cells were tested for object selectivity in a fixation task and a delayed match to sample task (DMTS), only 5 of 65 neurons had selectivity in both tasks (Peng et al 2008). When only most and least preferred shapes in the two tasks were compared, selectivity seemed largely consistent, but when the order of preference across the range of shapes was compared, the correspondence was far less consistent.…”
Section: Discussionmentioning
confidence: 99%
“…At the single-neuron level, we first focused our analysis on neurons that were shape selective in both tasks (n ϭ 11). We used a procedure similar to that described by Peng et al (2008) to determine whether individual neurons were selective for the same shapes in each task. For each neuron, we selected the two most preferred shapes and one least preferred shape in the single step.…”
Section: ϫ8mentioning
confidence: 99%
“…However, recent studies have revealed that FEF neurons can have visual responses that are selective to stimulus shape (Peng et al, 2008), and monkeys can detect microstimulation of the FEF at intensities well below the levels needed to trigger saccades (Murphey and Maunsell, 2008). Both these results suggest that FEF may be closer to sensory analysis than previously believed.…”
Section: Introductionmentioning
confidence: 85%